Fitness and Performance Testing of Male and Female Beach Soccer Players—A Preliminary Investigation - Larsen, Malte N.; Ermidis, Georgios; Brito, João; Ørner, Cecilie; Martins, Clarice; Lemos, Luís Filipe; Krustrup, Peter; Rago, Vincenzo (Frontiers in Sports and Active Living, 2021)
Purpose. This study aimed to compare performance on sand and a firm surface and to describe the physical capacity of male and female beach soccer players. Methods. 66 male and 29 female competitive beach soccer players voluntarily participated in this study. Firstly, within-subjects test scores were compared to scores on a firm surface (criterion validity; n=15 men) and reconducted on a second occasion (reliability; n=51 men). Secondly, the best score on sand was retained to compare test performance between ages (classified as below 20, 20 to 30, and above 30 yrs.) and sexes. Performance assessments included sprint time over 5 and 15 m (once on a firm surface and twice on sand), standing long jump (SLJ, once on a firm surface and twice on sand) and Yo-Yo intermittent recovery level 1 (Yo-Yo IR1, once on a firm surface and once on sand; only data for men were available). Results. 5-m sprint and Yo-Yo IR1 performance on sand were not correlated to performance on a firm surface (P>0.05). Test-retest reliability was acceptable for the 15-m sprint and SLJ tests (ICC>0.90; CV<5%). Performance in 15-m sprint and maximal sprinting speed were moderately lower in male players aged above 30 yrs. compared to players aged below 30 yrs. (d = 0.35 to 0.42; P<0.05). Irrespective of the age group, weight-bearing power-based performance mass was moderately to very largely higher in male players than in female players (d = 0.42 to 0.88; P<0.05). Conclusions. The lack of a consistent relationship between performance on sand and on a firm surface might indicate the need to develop specific test batteries for sand-based athletes. Age-related differences in physical performance were evident only in sprint capacity. Further studies are warranted to elucidate our preliminary findings and to develop the sand specific tests.